أثر المنظمات المتعلمة في تشجيع التميز المؤسسي دراسة تطبيقه في الهيئة الليبية للبحث العلمي (Comprehensive Journal of Science, 2026)
This study addressed the impact of learning organizations in promoting organizational excellence, focusing on the Libyan Scientific Research Authority as a case study. It aimed to analyze the reality of applying the characteristics of a learning organization—personal mastery, mental models, shared vision, team learning, and systems thinking—and to measure the level of organizational excellence manifested in the dimensions of leadership, strategic planning, human resource management, process management, and beneficiary satisfaction. Furthermore, it sought to uncover the nature of the relationship and the impact between these variables.The study adopted a descriptive-analytical and survey methodology. Its population included senior managers, department heads, office managers, and unit heads at the Libyan Scientific Research Authority. Data were collected using a specially designed questionnaire distributed to a purposive stratified sample of (34) individuals. Data analysis was conducted using the Statistical Package for the Social Sciences (SPSS), applying a range of statistical methods such as descriptive statistics, T-Test, Pearson correlation coefficient, and simple and multiple linear regression analyses.The study yielded several key findings. The level of application of learning organization characteristics in the Authority was relatively high, with an overall arithmetic mean of (3.58). The systems thinking dimension ranked first among the dimensions, while team learning ranked last with a moderate score. Results also indicated that the level of organizational excellence in the Authority was moderate. The leadership dimension ranked highest, while the dimensions of human resource management, process management, and beneficiary satisfaction recorded moderate to relatively low levels. Regarding hypothesis testing, multiple regression analysis results revealed a statistically significant positive impact of the combined learning organization characteristics on organizational excellence, explaining (54.9%) of the variance in the excellence level. Simple regression analysis further showed a statistically significant positive impact of mental models, shared vision, team learning, and systems thinking on organizational excellence. However, the personal mastery dimension did not show a statistically significant effect. The systems thinking dimension exhibited the strongest and most statistically significant influence in explaining the variance in organizational excellence.Based on the findings, the study concluded with several practical recommendations. These include enhancing organizational team learning by activating cross-functional work teams, developing human resource management systems—particularly improving the fairness and transparency of performance appraisals—investing in developing systems thinking and positive mental models among leaders and employees through specialized training programs, and finally, strengthening the link between shared vision and strategic planning by involving employees in goal formulation and implementation monitoring to ensure the sustainability of organizational excellence.
Keywords: Learning Organizations, Organizational Excellence, Libyan Scientific Research Authority, Organizational Learning, Leadership, Strategic Planning, Human Resource Management.